HUBUNGAN BERAT BADAN DENGAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI SMK N 6 PURWOREJO KABUPATEN PURWOREJO - Nur Sholichah; Larissa Ika Pramiswari (Jurnal Komunikasi Kesehatan, 2022)
The menstrual cycle starts from the first day until the next menstruation comes. In SMKN 6 Purworejo students who are overweight and obese I affect the occurrence of menstrual cycle disorders. The purpose of this study was to determine the relationship between body weight and menstrual cycle in adolescent girls at SMKN 6 Purworejo. This research method uses observational analytic with cross sectional approach. The research population was 106 students at SMKN 6 Purworejo, with a simple random sampling of 84 students. Data collection techniques with checklists. The analysis of this study used the chi-square test with computerized SPSS Version 25.00 program. The results of this study indicate that the results of the significance of p (0.000) < (0.05), the conclusion is that there is a relationship between body weight and the menstrual cycle in adolescent girls at SMKN 6 Purworejo, so there is a relationship between body weight and menstrual cycles in adolescent girls at SMKN 6 Purworejo.